Digital currents : how technology and the public are shaping TV news - Bivens, Rena, 1980- (University of Toronto Press, 2014)
Rena Bivens takes the reader inside TV newsrooms to explore how news organisations are responding to the paradigmatic shifts in media and communication practices.